1989
DOI: 10.1017/s0950268800030910
|View full text |Cite
|
Sign up to set email alerts
|

Direct transmission of Escherichia coli from poultry to humans

Abstract: SUMMARYEight hundred and sixty-four Escherichia coli isolates from workers at the University of Ibadan Teaching and Research Poultry Farm, and 216 isolates from poultry attendants at a commercial poultry farm in the city were found to be resistant to streptomycin, sulphafurazole and tetracycline. In contrast, all 576 and 288 E. coli isolates from village fowls and from villagers respectively were sensitive to these drugs. Isolates from birds in a modern university poultry unit (3744) exhibited the same resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…In 1989 a similar study of poultry and farm personnel (186) documented increased antimicrobial resistance in commercially reared birds compared to freerange village poultry. In this study, similar resistance patterns were isolated among poultry personnel and birds but not in village controls (186). Nijsten et al (187) demonstrated the ability of fecal Es.…”
Section: Antimicrobial Resistancesupporting
confidence: 75%
“…In 1989 a similar study of poultry and farm personnel (186) documented increased antimicrobial resistance in commercially reared birds compared to freerange village poultry. In this study, similar resistance patterns were isolated among poultry personnel and birds but not in village controls (186). Nijsten et al (187) demonstrated the ability of fecal Es.…”
Section: Antimicrobial Resistancesupporting
confidence: 75%
“…If the fecal-oral route is a possible means by which urovirulent E. coli come to inhabit the human intestine, it would seem important to determine what food might serve as their vehicle. Poultry is a candidate vehicle based on the findings of others (Levy et al, 1976;Linton et al, 1977;Ojeniyi, 1989;van den Bogaard et al, 2002;Johnson et al, 2003) that show transmission of avian E. coli from poultry to humans or similarities between avian E. coli and UPEC. Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the similarities of UPEC and APEC in their serogroups, virulence genotypes and assignments to phylogenetic groups (Johnson et al, 1998(Johnson et al, , 2001aKaper et al, 2004;Mokady et al, 2005;Johnson et al, 2006a;Moulin-Schouleur et al, 2006). It has been proposed that poultry may be a candidate vehicle for E. coli capable of causing human urinary tract disease, based on research showing transmission of avian E. coli from poultry to humans or similarities between avian E. coli and UPEC (Levy et al, 1976;Linton et al, 1977;Ojeniyi, 1989;van den Bogaard et al, 2002). Although previous studies have compared the content of virulence genes between UPEC and APEC, similarities of expression of the specific virulence genes of UPEC and APEC in the same chicken challenge model and/or murine UTI model have not to our knowledge been reported before.…”
Section: Discussionmentioning
confidence: 99%